PENGATURAN PEMBERDAYAAN PEREMPUAN MELALUI STRATEGI PENGARUSUTAMAAN GENDER: Regulations For Women's Empowerment Through Gender Mainstreaming Strategy - Ramadhina, Fadya; Retnowulandari, Wahyuni (Faculty of Law, Universitas Trisakti, 2025)
Poverty in Indonesia has an impact on women and is a problem that causes women to be trapped in a cycle that is difficult to break. Banten Province, which is experiencing rapid urbanization, faces major challenges in dealing with poverty. Tangerang City, as one of the economic centers in this province, shows social inequality. For this reason, the central and regional governments have issued various regulations and policies to improve gender equality, as contained in the 1945 Constitution of the Republic of Indonesia and CEDAW as the main instrument for the principle of equal rights. The research has a problem formulation, namely to determine the implementation of women's empowerment policies as intended in Tangerang City Regional Regulation Number 5 of 2018 and aims to describe the implementation of women's empowerment policies as intended in Tangerang City Regional Regulation Number 5 of 2018. This research focuses on the arrangements/regulations made Tangerang City regional government to show women's empowerment to achieve gender equality in areas experiencing poverty in Tangerang City. This research uses a normative type with a descriptive nature and then draws conclusions deductively. Based on the research results, the implementation of the Women's Empowerment policy is still hampered and has not been implemented evenly, which means that there are still many women in the city of Tangerang who have not experienced this policy to eradicate poverty in the City of Tangerang in order to create justice and equality regardless of gender.